Arsenic – Not an Obsolete Homicidal Poison - Pillay, Roshni; Sasidharan, Anu; Pillay, V V (Journal of Indian Academy of Forensic Medicine, 2020)
Arsenic has been one of the heavy metals with a notorious reputation as an ideal homicidal poison, with numerous high profile cases being reported in literature. It has also been a favourite with detective fiction writers who write stories on cases involving the use of poisons. However, over a period of time the popularity of arsenic began to wane in reality as well as in fiction; and other newer and more exotic poisons emerged. In recent times, cases of such homicidal attempts with this agent have become quite scarce in literature. It is in the midst of such a scenario that a shocking case of attempted murder with an arsenic compound came to light in a major corporate hospital of Cochin, involving a Keralite male working in Bengaluru city. Suspicions of systematic poisoning with arsenic trioxide through his food over a period of several days to weeks became a certainty on the basis of his gradually deteriorating health, medical evaluation, and subsequent laboratory investigations. While the case is yet to be resolved in the legal context, medically the patient is on the road to recovery, and this paper seeks to present the clinical unfolding of a case of arsenic poisoning with almost textbook characteristics in relation to symptomatology and laboratory findings. This disturbing case serves to demonstrate the sinister fact that some poisons just do not fade into history, and physicians must always be alert to the possibility of them still being employed by people with a criminal bent of mind.